2023
DOI: 10.3847/psj/accf11
|View full text |Cite
|
Sign up to set email alerts
|

Lorenz Energy Cycle: Another Way to Understand the Atmospheric Circulation on Tidally Locked Terrestrial Planets

Abstract: In this study, we employ and modify the Lorenz energy cycle (LEC) framework as another way to understand the atmospheric circulation on tidally locked terrestrial planets. It well describes the atmospheric general circulation in the perspective of energy transformation involved with several dynamical processes. We find that on rapidly rotating, tidally locked terrestrial planets, the mean potential energy (P M) and eddy potential energy (P E) are comparable to those on Earth… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 69 publications
0
1
0
Order By: Relevance
“…Ref. [9] employed a modified Lorenz energy cycle (LEC) framework to understand the atmospheric circulation on tidally locked terrestrial planets. They found that both the baroclinic path (associated with strong baroclinic instabilities) and the barotropic path (associated with Hadley cells) are efficient.…”
Section: Introductionmentioning
confidence: 99%
“…Ref. [9] employed a modified Lorenz energy cycle (LEC) framework to understand the atmospheric circulation on tidally locked terrestrial planets. They found that both the baroclinic path (associated with strong baroclinic instabilities) and the barotropic path (associated with Hadley cells) are efficient.…”
Section: Introductionmentioning
confidence: 99%